Autoimmune Hepatitis: A Review with emphasis on its histomorphology - Pradhan, SV (Journal of Pathology of Nepal, 2012)
Autoimmune hepatitis is a chronic inflammatory disorder characterized by periportal inflammation, hypergammaglobulinemia with elevated autoantibodies, and a dramatic response to immunosuppression. Various environmental and genetic influences can trigger the immune mediated destruction of the liver. A plethora of clinical presentations can be seen ranging from chronic indolent disease to fulminant hepatic failure. Autoimmune hepatitis does not have a pathognomonic feature, and its laboratory, serologic, and histologic manifestations are found in acute and chronic liver disease of diverse causes. Difficulties in distinguishing toxic, drug-related, virus-induced, and autoimmune causes of severe acute liver injury can result in misclassification. Our paper discusses autoimmune hepatitis, giving a detailed overview of its clinical presentation, immunopathogenesis, emphasis on histomorphological changes and the diagnostic criteria. Journal of Pathology of Nepal (2012) Vol. 2, 317-323 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6887